UNDERSTANDING THE BARRIERS: GROCERY STORES AND VISUALLY IMPAIRED SHOPPERS (Journal of Accessibility and Design for All, 2015)
The Accessibility for Ontarians with Disabilities Act, 2005 (AODA) is legislation that aims toward having complete accessibility within the province of Ontario by the year 2025. The accessible built environment is one of the key areas covered by the legislation; therefore, grocery stores, as part of the built environment, should be designed to accommodate shoppers with different abilities.Grocery stores include many different zones and services with the aisles area being one of the main barriers to access for people with impaired vision.  This area features many different sections such as canned goods, dry packaged goods, spices, drinks and snacks, baking supplies, baby items, cereals, cleaning products, pet supplies, and health and beauty items.  For visually impaired individuals, however, it can be hard to reach these various sections and to find the relevant products.  The purpose of this paper is to present a study that sought to understand the barriers that shoppers with vision impairment (VI) face in the grocery store`s built environment. The research approach was based on the application of the ethnography method, Think-aloud Protocol (TAP), Interviews, and behavioural mapping method.